Herbs : essential know-how and expert advice for gardening success - Mahon, Stephanie (DK grow., 2022)
Ideal for first-time gardeners, Grow Herbs contains everything you need to know to grow a wide variety of perennial and annual herbs. Learn how to sow, grow, harvest, and propagate your plants, with advice on caring for home-grown herbs as well as tips on making the most of store-bought pots. Explore a huge variety of herbs available to home gardeners with a wide-ranging directory, including popular herbs such as mint, basil, and sage as well as lesser-grown options like shiso and bergamot.--